Oak tree-ring carbon stable isotopes from eastern Europe reveal significant drought signals along elevational gradients - Sochová, Irena; Kolář, Tomáš; Koňasová, Eva; Urban, Otmar; Pernicová, Natálie; Trnka, Miroslav; Bošeľa, Michal; Marčiš, Peter; Büntgen, Ulf; Rybníček, Michal (The Science of the total environment, 2024)
The importance of stable carbon and oxygen isotopes in tree-ring-based climate reconstructions is increasingly recognized, especially in regions where traditional dendrochronological parameters, such as tree-ring width, usually fail. However, the effects of elevation and other site conditions on climate signals in tree-ring stable isotope (TRSI) chronologies remain unclear. Here, we assess the sensitivities to precipitation and drought of tree-ring width (TRW) and δ13C and δ18O TRSI chronologies of 136 living oaks (Quercus spp.) from five different elevational zones between 130 and 630 m asl in eastern Slovakia. Our results show that while the mean δ13C values were stable across the elevational gradient, TRW gradually decreased with increasing elevation, and the mean δ18O values significantly differed between the lower and higher sites. Despite these variations, we observed strong coherency among all the elevation-specific TRW and TRSI chronologies. We also found that mainly mid-May to July precipitation and mid-May to August drought controlled TRW and the δ13C values, whereas the δ18O reflected an overall lower climate signal. Our results show a relatively stable drought signal across the elevational range, with shorter seasonal response windows at higher elevations. Furthermore, our study indicates that carbon TRSI and TRW oak chronologies capture distinct summer drought signals independently of elevation and therefore have a strong paleoclimatic potential across eastern Europe.
Keywords: Climate Change; izotopy uhlíku; Droughts; klimatické změny; monitorování životního prostředí; Stable isotopes; Paleoclimate; období sucha; Slovakia; Carbon Isotopes; Altitude; dub (rod); Oxygen Isotopes; nadmořská výška; stromy; Quercus; Hydroclimate; Tree rings; izotopy kyslíku; podnebí; Environmental Monitoring; Slovenská republika; Climate; Trees; Dendrochronology; Eastern Europe